TINJAUAN HUKUM TERHADAP KEBIJAKAN PENANGGULANGAN (COUNTERMEASURE POLICIES) PANDEMI CORONOVIRUS DISEASE 2019 (COVID-19) PADA SEKTOR KETENAGAKERJAAN (KARTU PRAKERJA DAN DUKUNGAN VOKASI MELALUI SUPER TAX DEDUCTION) - Bagaskoro Arif Prabowo (SUPREMASI HUKUM, 2021)
Employment problems derived from COVID-19 pandemic urge every nation to enact countermeasure policy. Government of Indonesia through promulgating and/or enacting Presidential Regulation Number 76 of 2020, Government Regulation Number 45 of 2019, Minister of Finance Regulation Number 153/PMK.010/2020, and Minister of Finance Regulation Number 128/PMK.010/2019 formulates countermeasure policies for pandemic’s impact on employment, which are pre-employment card and vocational support through Super Tax Deduction. However, it must be tested for its relevance in the enactment process. This study conducted in normative legal research which based on study of documents and used various legal sources of information. The results show that the regulations are relevant for its role as countermeasure policies to overcome pandemic’s impact on employment and are interconnected with higher disaster management and recovery regulations. Keywords: countermeasure policy; COVID-19 pandemic; employment.